KECEMASAN DAN STRES MATERNAL DAN HUBUNGANNYA PADA IBU HAMIL DI LIMBANGAN KENDAL - Rahayu, Hermeksi; Kustriyanti, Dwi (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Pregnant women often experience anxiety, which can be detrimental to the emotional, psychological, and social development of their unborn children. Perinatal problems for both mother and child are more common when anxiety is present during pregnancy. Furthermore, it has frequently been demonstrated that the onset of anxiety during these periods precedes the onset of depression. Antenatal depression has been linked to a higher incidence of surgical deliveries, pre-eclampsia, and spontaneous abortion. Mothers who suffer from depression have a higher probability of having preterm births, lower birth weights, lower Apgar scores, and less frequent and shorter breastfeeding sessions. This study aims to assess maternal stress and anxiety and their association among pregnant women. Purposive sampling was used to gather cross-sectional data from 172 pregnant women in Limbangan, Kendal, in June–August 2024. Women with stress and anxiety who were willing to participate in the survey and did not have communication problems met the inclusion criteria. Pregnant women using antidepressants and those in low-income circumstances were excluded. Maternal stress and anxiety during pregnancy were observed in this study. Participants completed the Overall Anxiety Severity and Impairment Scale and the Pregnancy-Related Anxiety Scale (PRAS), which are tools used to evaluate pregnant women's stress and anxiety levels. One-way ANOVA, Pearson correlation, frequency distribution, and measures of central tendency (mean, standard deviation, minimum, and maximum values) were used in the statistical analysis. The results of this study indicate that maternal anxiety is highest in Trimester I (mean 30.80 ± 6.21) and stress is highest in Trimester II (mean 7.29 ± 4.28). There was a significant correlation between maternal anxiety and stress (P-value = 0.016). The presence of anxiety during pregnancy has been associated with a higher incidence of perinatal complications for both mother and child. In addition, the appearance of anxiety during these periods has been shown to precede the development of depression on a high percentage of occasions. The causes of anxiety in pregnant women are related to concerns about giving birth to a disabled child and changes in appearance after delivery. Thus, multiple approaches to reducing anxiety are required.